WAYS CONSTITUENCY DEVELOPMENT FUND (CDF) PROMOTES STUDENTS' ACCESS TO SECONDARY SCHOOL EDUCATION IN GITHUNGURI SUB-COUNTY, KENYA - Rukwaro, Muthoni; Olembo, Prof. Jothem; Ogeta, Dr.Norbert (African Journal of Education and Practice, 2017)
Purpose: Kenya started offering secondary school education as part of her basic education in 2008 through subsidization of tuition fee. Nevertheless, this was not adequate due to the fact that secondary education was more costly and this has made many students especially from humble background fail to access and complete secondary education. All students must have access to and complete a full course of schooling to eliminate social and economic barriers, and gender disparity. The study was carried out to establish the influence of CDF on access to secondary school in Githunguri Sub-County, Kenya. The objectives of the study were: to find out the extent to which projects were funded through CDF, to assess the benefits of CDF projects in the school, and to evaluate the number of students per class. Methodology: This study was conducted using descriptive survey. The study was carried out on a population of 20 public secondary schools which were randomly sampled from a total of 33 schools. Purposive sampling was used to sample 40 class teachers and 20 principals, while simple random sampling was used to select 320 students in forms three and four. Questionnaires and interview guides were used to collect data. The research tools were piloted in a neighbouring school using test-retest method. Quantitative data were organized with the aid of SPSS and analyzed using descriptive statistics such as frequencies and percentages. Data was presented in graphs and tables. Qualitative data were arranged thematically and discussed based on the study objectives. Findings: The study found out that even though CDF has improved the status of schools through the building of classes, laboratories and dormitories, access to secondary schools in the Sub-County is low with transition rate at 56.9% in 2014 which is below the target of the Ministry of Education of 70% by 2015. Recommendations: The study recommended that Constituency Development Funds should be used to establish more day schools than boarding schools because they are more accessible to the poor than boarding schools.